2016
DOI: 10.1371/journal.pone.0159826
|View full text |Cite|
|
Sign up to set email alerts
|

Shikonin Suppresses NLRP3 and AIM2 Inflammasomes by Direct Inhibition of Caspase-1

Abstract: Shikonin is a highly lipophilic naphtoquinone found in the roots of Lithospermum erythrorhizon used for its pleiotropic effects in traditional Chinese medicine. Based on its reported antipyretic and anti-inflammatory properties, we investigated whether shikonin suppresses the activation of NLRP3 inflammasome. Inflammasomes are cytosolic protein complexes that serve as scaffolds for recruitment and activation of caspase-1, which, in turn, results in cleavage and secretion of proinflammatory cytokines IL-1β and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…Caspase-1 mediates proinflammatory programmed cell death in response to exogenous and endogenous stimuli to protect cells. Caspase-1 dysfunction is closely associated with different diseases 37,38 . The results of the current study show that caspase-1 expression was increased in short-wavelength blue light-exposed rat lens cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1 mediates proinflammatory programmed cell death in response to exogenous and endogenous stimuli to protect cells. Caspase-1 dysfunction is closely associated with different diseases 37,38 . The results of the current study show that caspase-1 expression was increased in short-wavelength blue light-exposed rat lens cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical inflammasome includes NLR (including NLRP1, NLRP3 and NLRC4) and non-NLR (e.g. AIM2) types, which is mediated by activation of caspase-1 in response to pathogen-associated molecular patterns and damage-associated molecular pattern molecules ( 24 , 25 ). Sester et al ( 26 ) reported that AIM2 antagonist protein p202 had a high expression and low IL-1β output in response to transfected DNA and mouse CMV infection in an autoimmune hemolytic anemia model.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1 also mediates proinflammatory programmed cell death, also termed pyroptosis, in response to exogenous and endogenous stimuli to protect cells. Caspase-1 is not only activated in immune cells, but is also activated in epithelial and mesenchymal cells (26), and dysfunction of caspase-1 is closely associated with various diseases (27,28). However, whether pyroptosis of lens epithelial cells is implicated in the initiation and progression of non-congenital cataracts in humans remains to be established.…”
Section: Discussionmentioning
confidence: 99%